2004
DOI: 10.21236/ad1003886
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Total Longshore Sediment Transport Rates on Incident Wave Parameters and Breaker Type

Abstract: PURPOSE:Total longshore sediment transport (LST) rate and its cross-shore distribution in the surf zone are essential to many coastal engineering and science studies. Practical engineering applications such as predicting beach response in the vicinity of coastal structures, beach-fill evolution and renourishment requirements, and sedimentation rates in navigation channels all require accurate predictions of LST rates. Present predictive tools have been developed based primarily on field studies; however, obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Previous studies have found that a significant part of the longshore sediment transport occurs in the swash zone and may account for a large portion of the total littoral drift (Bodge and Dean, 1987, Kamphuis, 1991, Smith et al, 2009, especially on steep reflective beaches (Van Wellen et al, 2000), where alongshore sediment transport in the swash zone can be significantly greater than that in the surf zone (Hughes et al, 2007). In the present study, model predicted alongshore swash-zone transport may account for 34%-100% of the total littoral drift under the wave conditions simulated at the study site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have found that a significant part of the longshore sediment transport occurs in the swash zone and may account for a large portion of the total littoral drift (Bodge and Dean, 1987, Kamphuis, 1991, Smith et al, 2009, especially on steep reflective beaches (Van Wellen et al, 2000), where alongshore sediment transport in the swash zone can be significantly greater than that in the surf zone (Hughes et al, 2007). In the present study, model predicted alongshore swash-zone transport may account for 34%-100% of the total littoral drift under the wave conditions simulated at the study site.…”
Section: Discussionmentioning
confidence: 99%
“…Offshore and onshore sediment transport in the swash zone, therefore, contributes significantly to shoreline accretion and erosion. Secondly, a significant part of the longshore sediment transport occurs in the swash zone and may account for a large portion of the total littoral drift (Bodge and Dean, 1987, Kamphuis, 1991, Smith et al, 2009, especially on steep reflective beaches (Van Wellen et al, 2000), where the surf zone is typically narrow or even absent, with wave breaking occurring practically on the beachface. Alongshore sediment transport in the swash zone can be significantly greater than that in the surf zone on such beaches (Hughes et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the simplified bulk formulations fail to account for morphological features on the beach that affect the breaking type of waves and accuracy of LST rate predictions (Kamphuis and Readshaw, ; Smith et al ., ). As an example, if plunging breaking were more frequent than spilling for the more energetic conditions which in turn generate the larger transport rates, then one of the main hypotheses of the bulk expressions (spilling breaking) would not be fulfilled (Smith et al ., ). Yet, the results from bulk equations are still highly variable when averaged for the period 1995–2017, characterized by a more typical beach morphological setting (Table ).…”
Section: Comparison With Predictions From Bulk Equationsmentioning
confidence: 98%
“…However, the wave propagation processes were altered by a submerged nearshore bar welding to the beach during the initial development of the modern delta (until ~1995; see Supporting Information and Garel et al ., ). Moreover, the simplified bulk formulations fail to account for morphological features on the beach that affect the breaking type of waves and accuracy of LST rate predictions (Kamphuis and Readshaw, ; Smith et al ., ). As an example, if plunging breaking were more frequent than spilling for the more energetic conditions which in turn generate the larger transport rates, then one of the main hypotheses of the bulk expressions (spilling breaking) would not be fulfilled (Smith et al ., ).…”
Section: Comparison With Predictions From Bulk Equationsmentioning
confidence: 99%
See 1 more Smart Citation